2015
DOI: 10.1017/s0714980814000531
|View full text |Cite
|
Sign up to set email alerts
|

From Beginning to End: Perspectives of the Dementia Journey in Northern Ontario

Abstract: Research on dementia care continues to develop, yet little attention has been given to the dementia experience in rural, northern communities. This study explored the dementia journey through the viewpoints of health service providers, caregivers, community members, and people living with dementia. The findings highlight the complexity of dementia awareness and understanding. Sound awareness and knowledge of dementia itself, the community services available, as well as of the perspectives of individuals living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 29 publications
1
30
0
2
Order By: Relevance
“…Numerous education and support needs were identified, with a general need for greater information or support for persons with dementia and their caregivers frequently mentioned in qualitative work (see Table 4). The need for education about available resources and services was often highlighted by participants, including service/health providers (Burton, O'Connell, & Morgan, 2016;Coogle, 2002;Di Gregorio, Ferguson, & Wiersma, 2015;Edelman et al, 2006;Forbes et al, 2012;Forbes et al, 2006;Gurayah, 2015;Glueckauf et al, 2005;Innes, Szymczynska, & Stark, 2014;O'Reilly & Strong, 1997;Smith et al, 2011). When needs were ranked by importance or frequency, the top reported needs included information on dementia in general, treatments, coping with responsive behaviours and challenging symptoms, meaningful activities for the person with dementia, resources/supports, and caregiving and family dynamics (Buettner & Langrish, 2001;Coogle, 2002;Edelman et al, 2006).…”
Section: Education and Support Service Needs Availability And Usementioning
confidence: 99%
See 2 more Smart Citations
“…Numerous education and support needs were identified, with a general need for greater information or support for persons with dementia and their caregivers frequently mentioned in qualitative work (see Table 4). The need for education about available resources and services was often highlighted by participants, including service/health providers (Burton, O'Connell, & Morgan, 2016;Coogle, 2002;Di Gregorio, Ferguson, & Wiersma, 2015;Edelman et al, 2006;Forbes et al, 2012;Forbes et al, 2006;Gurayah, 2015;Glueckauf et al, 2005;Innes, Szymczynska, & Stark, 2014;O'Reilly & Strong, 1997;Smith et al, 2011). When needs were ranked by importance or frequency, the top reported needs included information on dementia in general, treatments, coping with responsive behaviours and challenging symptoms, meaningful activities for the person with dementia, resources/supports, and caregiving and family dynamics (Buettner & Langrish, 2001;Coogle, 2002;Edelman et al, 2006).…”
Section: Education and Support Service Needs Availability And Usementioning
confidence: 99%
“…Poor awareness of available or eligible services was described within six articles, spanning Canada, the United States, and Scotland (Di Gregorio et al, 2015;Forbes et al, 2006;Glueckauf et al, 2005;Herron et al, 2016;Innes et al, 2014;Morgan et al, 2002). Di Gregorio et al (2015) concluded that a lack of awareness regarding services was common, and that there were limited presence and visibility of organizations providing dementia-related education and support in rural northern communities. Service providers reported higher visibility of their dementia-related support and education services in urban compared to rural areas, with lack of knowledge as a barrier to use (Herron et al 2016).…”
Section: Knowledge Of Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fragmented service systems havebeen found to have a negative impact on rural carers who seek to access and navigate services for people with dementia (Orpin, Stirling, Hetherington & Robinson, 2014;Peel & Harding, 2014;Morgan et al, 2014;Di Gregorio, Ferguson & Wiersma, 2015). Barriers to accessing services include health professionals and carers' lack of awareness of services (Di Gregorio et al, 2015;Hansen, Robinson, Mudge & Crack, 2005) and lack of communication between professionals and with carers (Hansen et al, 2005).…”
Section: Introduction (5304)mentioning
confidence: 99%
“…Barriers to accessing services include health professionals and carers' lack of awareness of services (Di Gregorio et al, 2015;Hansen, Robinson, Mudge & Crack, 2005) and lack of communication between professionals and with carers (Hansen et al, 2005).…”
Section: Introduction (5304)mentioning
confidence: 99%